Interactions of Bacillus thuringiensis strains for Plutella xylostella (L.) (Lepidoptera: Plutellidae) susceptibility - Santos, Mariana Sanguinete; Dias, Naymã Pinto [UNESP]; Costa, Lilian Lucia; De Bortoli, Caroline Placidi [UNESP]; Souza, Eduardo Henrique; Ferreira Santos, Annelyse Cristina; De Bortoli, Sergio Antonio [UNESP]; Polanczyk, Ricardo Antonio [UNESP] (Elsevier, 2019)
Bacillus thuringiensis (Bt) biopesticides are an environmentally safe alternative to the management of Plutella xylostella pesticide resistance evolution. We evaluated P. xylostella susceptibility to six Bt strains cultivated and applied individually, and 15 combinations of Bt strains mixed after cultivation. Three combinations resulted in synergism and one in antagonism. Promising results of larval mortality with synergistic effects were obtained with the combinations Bt var. thuringiensis strain HD-2 + Bt finitimus strain HD-3, Bt var. thuringiensis strain HD-2 + Bt dendrolimus strain HD-7 and Bt var. thuringiensis strain HD-2 + Bt var. aizawai strain HD-11.
Keywords: Cry toxins; Diamondback moth; Microbial control; Synergism